1998
DOI: 10.1016/s0378-1097(98)00260-2
|View full text |Cite
|
Sign up to set email alerts
|

Soluble fumarate reductase isoenzymes from Saccharomyces cerevisiae are required for anaerobic growth

Abstract: In Saccharomyces cerevisiae, the cytosolic and promitochondrial isoenzymes of fumarate reductase are encoded by the FRDS and OSM1 genes, respectively. The product of the OSM1 gene is reported to be required for growth in hypertonic medium. Simultaneous disruption of the FRDS and OSM1 genes resulted in the inability of the yeasts to grow anaerobically on glucose as a carbon source, and disruption of the OSM1 gene caused poor growth under anaerobic conditions. However, the disruption of both the FRDS and/or OSM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…We further found that both OSM1 and FRD1, encoding fumarate reductase, were upregulated under anaerobic conditions. It was reported that a single deletion of either OSM1 or FRD1 does not affect the anaerobic cell growth (40), whereas a double deletion is lethal under anaerobic conditions but has no growth effect under aerobic conditions (41), and it was suggested that fumarate reductase is essential under anaerobic conditions because it catalyzes the only reaction that could oxidize free FADH 2 under these conditions (40). Here, we propose that the FAD that is reduced to FADH 2 by accepting electrons from protein folding in the ER is then oxidized back to FAD by the fumarate reductase.…”
Section: Figmentioning
confidence: 99%
“…We further found that both OSM1 and FRD1, encoding fumarate reductase, were upregulated under anaerobic conditions. It was reported that a single deletion of either OSM1 or FRD1 does not affect the anaerobic cell growth (40), whereas a double deletion is lethal under anaerobic conditions but has no growth effect under aerobic conditions (41), and it was suggested that fumarate reductase is essential under anaerobic conditions because it catalyzes the only reaction that could oxidize free FADH 2 under these conditions (40). Here, we propose that the FAD that is reduced to FADH 2 by accepting electrons from protein folding in the ER is then oxidized back to FAD by the fumarate reductase.…”
Section: Figmentioning
confidence: 99%
“…Recently, we constructed disruptants of the FRDS and OSM1 genes [9,10]. The OSM1 disruptant (DOSM) grew more slowly than DBY747 under anaerobic conditions, and the disruptant of both the FRDS and OSM1 genes (DFRDOSM) failed to grow at all.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we constructed disruptants of the FRDS and OSM1 genes [9,10]. The OSM1 disruptant (DOSM) grew more slowly than DBY747 under anaerobic conditions, and the disruptant of both the FRDS and OSM1 genes (DFRDOSM) failed to grow at all.…”
Section: Introductionmentioning
confidence: 99%